ISLAM DAN DAMAI (Kajian atas Pluralisme Agama dalam Islam) - Ismail, Roni (UIN Sunan Kalijaga Yogyakarta, 2013)
The latest cases of religious based violence have placed Islam as a religion of terror. This is simply because the fact that some terror actions were done by people call themselves muslim. What make it even worse is that the cases have been exaggerated and blown up by international big mass medias which become the main source of the news throughout the world. Yet the very spirit of peace as observed by muslim majority has often been neglegted by these mass medias. This paper is an attempt to promote peace Islam through one of the main teachings of Islam, namely the Islamic teaching of religious pluralism. The result is that both normative and historic Islam reject violence without any acceptable reason. Islam teaches peace as a fun- damental theological view and code of conduct.Al-Quran nor matively teaches the basic principles of pluralism in race, ethnicity, or religion. Plurality in Islam is seen as sunnatullah. Islam therefore promotes tolerance, prohibits any form of religious coercion, and requires Muslims to maintain the holy places such as churches, synagogues and mosques. Al-Quran also teaches the prin- ciples of the religious fraternity among Ahli Kitab-who have book of God.Historically, the first generation of Muslims who lived at the time of the Prophet Muhammad implemented Islamic plurality view in the Medina Charter. This charter in turn had instigated peace among the elements of Medina community. As a result, there were no racial tensions or religious conflicts occurred, as was no predominantly Muslim terror in its various form shappened over the minority.The study of religious pluralism in Islam therefore describes Islam as a religion of non-violence and terror, but as a religion of peace.